Temporal dynamics of macrophage transcriptional profiles during zebrafish wound healing - Begon-Pescia, Christina; Manchon, Laurent; Özbilgiç, Resul; Boireau, Stéphanie; Louis, Anaïs; Georges, Simon; Nguyen-Chi, Mai (Frontiers in Immunology, 2026)
IntroductionMacrophages participate in wound healing by contributing to host defense and by orchestrating inflammation and repair. They adapt dynamically to the wound microenvironment by adopting diverse polarization states, which are determinant of wound outcome, influencing whether healing is successful or becomes chronic. The zebrafish embryo, widely used for live imaging of immune responses, is a powerful model to study macrophage behavior after injury. However, the transcriptional landscape of polarized macrophages in this model during wound healing remains insufficiently characterized.MethodsHere, we employed bulk RNA sequencing on FACS-sorted zebrafish macrophages at different times following tail fin wounding in larvae, a robust model for studying sterile inflammation. We analyzed gene expression changes over the time by comparing wounded versus unwounded conditions to characterize macrophage transcriptional programs during wound healing.ResultsOur findings reveal that zebrafish macrophages undergo large transcriptomic changes along different wound healing phases, particularly between 2 and 5 hours post-amputation, suggesting a fast reprogramming leading to different functional states. We further show that, at 2h, macrophages acquire a pro-inflammatory profile with a gene signature closed to M1-like program. At 5h, macrophages express genes involved in immunoregulation and healing, associated with shutoff of pro-inflammatory pathways and the activation of glucose and glycogen metabolism. Finally, we show that macrophage reprogramming becomes deeply attenuated by 29h post injury.DiscussionOur findings provide a foundation for understanding macrophage polarization in zebrafish, revealing underpinning molecular mechanisms that include both specific and evolutionarily conserved pathways with a potential impact on translational medicine.